Werneria spathulata, nuevo registro para la flora del Ecuador, y redescubrimiento de Xenophyllum acerosum - Petr Sklenář; Katya Romoleroux (Caldasia)
A new record of Werneria (Asteraceae) for Ecuador is reported, it is W. spathulata, a small, delicate, rhizomatous herb found in the páramos of Antisana Volcano. Moreover, rediscovery of Xenophyllum acerosum after 73 years in the Azuay province of southern Ecuador is documented. Images of both species and their habitats are provided.